Dietary Intake of Pleurotus eryngii Ameliorated Dextran‐Sodium‐Sulfate‐Induced Colitis in Mice. Issue 17 (29th May 2019) - Hu, Qiuhui; Yuan, Biao; Wu, Xian; Du, Hengjun; Gu, Min; Han, Yanhui; Yang, Wenjian; Song, Mingyue; Xiao, Hang
Abstract : Scope: Pleurotus eryngii, an edible mushroom, is widely consumed as a functional food for various health benefits due to its multiple bioactive components. There are growing interests in using whole‐food‐based strategies to prevent colonic inflammation via potential synergistic interactions among different components within the whole foods. However, limited research is focused on the inhibitory effects of the whole P. eryngii mushroom against inflammatory bowel disease (IBD). Methods and results: The protective effects of P. eryngii mushroom against IBD are determined in the dextran‐sodium‐sulfate‐induced colitis model in mice. Dietary administration of P. eryngii (1 and 3% w/w) alleviates colonic inflammation, which is evidenced by decreased disease index, increased colon length, and reduced pro‐inflammatory cytokines in the colonic mucosa. Sequencing the 16S rRNA genes of fecal microbiota demonstrates that P. eryngii mushroom significantly alters the structure of microbiota and partially reverses the shifts of fecal microbiota induced by DSS treatment. The levels of SCFAs in the cecum are increased by P. eryngii mushroom. Conclusion: Overall, the results demonstrate the anti‐inflammatory and microbiota‐modulating effects of P. eryngii mushroom as a whole‐food‐based ingredient against IBD, and its potential as a prebiotic agent to prevent inflammation‐related disorders in humans. Abstract : Edible mushrooms are used as functional and medicinal foods for various health benefits. The protective effects of Pleurotus eryngii mushroom against inflammatory bowel disease are determined using a colitis model in mice. Dietary administration of P. eryngii alleviates colonic inflammation, partially reverses the shifts of fecal microbiota induced by dextran sodium sulfate treatment, and significantly increases the levels of short‐chain fatty acids.